2020
DOI: 10.3897/zookeys.917.47444
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale species delimitation: speciation in process and periodic patterns in nudibranch diversity

Abstract: Using the nudibranch genus Amphorina as a model, ongoing speciation is demonstrated, as well as how periodic-like patterns in colouration can be included in an integrated method of fine-scale species delimitation. By combining several methods, including BPP analysis and the study of molecular, morphological, and ecological data from a large number of specimens within a broad geographic range from northern Europe to the Mediterranean, five species are recognised within the genus Amphorina, reviewed here for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…A major modern feature of this is the general denial of huge polytypic and pan-geographic species in favour of fine-scale interspecific morphological differences in combination with limited geographic ranges. Within restricted "narrow species" a polymorphism (a basis for the polytypic concept) is often manifested in the occurrence of parallel morphs, which may obscure species diversity (see e.g., Korshunova et al, 2020b). Though Mayr was among the major developers of the population-based, variable, "non-typological" species concept, he also admitted the possible existence of a hardly detectable diversity of "sibling species" (Mayr, 1942;Yoder et al, 2005).…”
Section: General Taxonomic and Biogeographic Overview Of The Family Dmentioning
confidence: 99%
“…A major modern feature of this is the general denial of huge polytypic and pan-geographic species in favour of fine-scale interspecific morphological differences in combination with limited geographic ranges. Within restricted "narrow species" a polymorphism (a basis for the polytypic concept) is often manifested in the occurrence of parallel morphs, which may obscure species diversity (see e.g., Korshunova et al, 2020b). Though Mayr was among the major developers of the population-based, variable, "non-typological" species concept, he also admitted the possible existence of a hardly detectable diversity of "sibling species" (Mayr, 1942;Yoder et al, 2005).…”
Section: General Taxonomic and Biogeographic Overview Of The Family Dmentioning
confidence: 99%
“…At the same time, modern taxonomical revisions and dedicated phylogenetic studies have not paid enough attention to this genus. During the last two decades only two contributions performed integration of morphological and molecular data within this group: (1) a recent revision of the family Fionidae (Cella et al, 2016) that evaluated Eubranchus as a member of this family and suggested that the amphiboreal Eubranchus rupium (Møller, 1842) represented a species complex of at least three distinct species; and (2) revision of the Eubranchus farrani (Alder et Hancock, 1844) -E. pallidus (Alder et Hancock, 1842) species complex (Korshunova et al, 2020) completed with a reinstatement of the generic name Amphorina for these molluscs and the description of two new species from the North-East Atlantic: Amphorina andra Korshunova et al, 2020 andA. viriola Korshunova et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…There were attempts to describe chromatic variants within another nudibranch family Chromodorididae under the term “colour groups” 58 or as different colour morphs in frames of a phylogeny 59 , 60 , but not in a periodic framework. However, when similar morphs of different closely related species are mapped in the same horizontal sections, the partial periodicity can be clearly revealed 18 .…”
Section: Discussionmentioning
confidence: 99%
“…chromatic variants) and also potentially not yet discovered morphs of the closely related species. Currently we have no information about which particular genes underlie any common genetic basis in the polychromatic nudibranchs 61 , but it must inevitably imply similar developmental genes basis and it was recently used for delineation of a very difficult nudibranch species complex of the genus Amphorina 18 . A North Pacific species, Polycera atra MacFarland, 1905, provides evidence for the existence of the underlying similar genomic basis, that appears in parallel in various phylogenetic lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation